Cardiac Magnetic Resonance Assessment of Interstitial Myocardial Fibrosis and Cardiomyocyte Hypertrophy in Hypertensive Mice Treated With Spironolactone - Coelho‐Filho, Otavio R. (J Am Heart Assoc, 2014)
BACKGROUND: Nearly 50% of patients with heart failure (HF) have preserved LV ejection fraction, with interstitial fibrosis and cardiomyocyte hypertrophy as early manifestations of pressure overload. However, methods to assess both tissue characteristics dynamically and noninvasively with therapy are lacking. We measured the effects of mineralocorticoid receptor blockade on tissue phenotypes in LV pressure overload using cardiac magnetic resonance (CMR). METHODS AND RESULTS: Mice were randomized to l‐nitro‐ω‐methyl ester (l‐NAME, 3 mg/mL in water; n=22), or l‐NAME with spironolactone (50 mg/kg/day in subcutaneous pellets; n=21). Myocardial extracellular volume (ECV; marker of diffuse interstitial fibrosis) and the intracellular lifetime of water (τ(ic); marker of cardiomyocyte hypertrophy) were determined by CMR T1 imaging at baseline and after 7 weeks of therapy alongside histological assessments. Administration of l‐NAME induced hypertensive heart disease in mice, with increases in mean arterial pressure, LV mass, ECV, and τ(ic) compared with placebo‐treated controls, while LV ejection fraction was preserved (>50%). In comparison, animals receiving both spironolactone and l‐NAME (“l‐NAME+S”) showed less concentric remodeling, and a lower myocardial ECV and τ(ic), indicating decreased interstitial fibrosis and cardiomyocyte hypertrophy (ECV: 0.43±0.09 for l‐NAME versus 0.25±0.03 for l‐NAME+S, P<0.001; τ(ic): 0.42±0.11 for l‐NAME groups versus 0.12±0.05 for l‐NAME+S group). Mice treated with a combination of l‐NAME and spironolactone were similar to placebo‐treated controls at 7 weeks. CONCLUSIONS: Spironolactone attenuates interstitial fibrosis and cardiomyocyte hypertrophy in hypertensive heart disease. CMR can phenotype myocardial tissue remodeling in pressure‐overload, furthering our understanding of HF progression.